Platelet‐Activating Factor Mediates the Cytotoxicity Induced by W7FW14F Apomyoglobin Amyloid Aggregates in Neuroblastoma Cells. Issue 12 (15th October 2014) - Sirangelo, Ivana; Giovane, Alfonso; Maritato, Rosa; Nunzia, D'Onofrio; Iannuzzi, Clara; Giordano, Antonio; Irace, Gaetano; Balestrieri, Maria Luisa
ABSTRACT W7FW14F apomyoglobin (W7FW14F ApoMb) amyloid aggregates induce cytotoxicity in SH‐SY5Y human neuroblastoma cells through a mechanism not fully elucidated. Amyloid neurotoxicity process involves calcium dyshomeostasis and reactive oxygen species (ROS) production. Another key mediator of the amyloid neurotoxicity is Platelet‐Activating Factor (PAF), an inflammatory phospholipid implicated in neurodegenerative diseases. Here, with the aim at evaluating the possible involvement of PAF signaling in the W7FW14F ApoMb‐induced cytotoxicity, we show that the presence of CV3899, a PAF receptor (PAF‐R) antagonist, prevented the detrimental effect of W7FW14F ApoMb aggregates on SH‐SY5Y cell viability. Noticeably, we found that the activation of PAF signaling, following treatment with W7FW14F ApoMb, involves a decreased expression of the PAF acetylhydroase II (PAF‐AH II). Interestingly, the reduced PAF‐AH II expression was associated with a decreased acetylhydrolase (AH) activity and to an increased sphingosine‐transacetylase activity (TAS) with production of N‐acetylsphingosine (C2‐ceramide), a well known mediator of neuronal caspase‐dependent apoptosis. These findings suggest that an altered PAF catabolism takes part to the molecular events leading to W7FW14F ApoMb amyloid aggregates‐induced cell death. J. Cell. Biochem. 115: 2116–2122, 2014. © 2014 Wiley Periodicals, Inc.